Site-Specific Regulated Memristors via Electron-Beam-Induced Functionalization of HfO2 - Kumar, Mohit; Ahn, Yeong Hwan; Iqbal, Shahid; Kim, Unjeong; Seo, Hyungtak (Small, 2022)
Emerging nonvolatile resistive switching, also known as the memristor, works with a distinct concept that relies mainly on the change in the composition of the active materials, rather than to store the charge. Particularly for oxide-based memristors, the switching is often governed by the random and unpredicted temporal/spatial migration of oxygen defects, resulting in possessing limitations in terms of control over conduction channel formation and inability to regulate hysteresis loop opening. Therefore, site specific dynamic control of defect concentration in the active materials can offer a unique opportunity to realize on-demand regulation of memory storage and artificial intelligence capabilities. Here, high-performance, site-specific spatially scalable memristor devices are fabricated by stabilizing the conduction channel via manipulation of oxygen defects using electron-beam irradiation. Specifically, the memristors exhibit highly stable and electron-beam dose-regulated multilevel analog hysteresis loop opening with adjustable switching ratios even higher than 104. Additionally, broad modulation of neural activities, including short- and long-term plasticity, paired-pulse facilitation, spike-timing-dependent plasticity, and dynamic multipattern memory processing, are demonstrated. The work opens a new possibility to regulate the resistive switching behavior and control mimicking of neural activities, providing a hitherto unseen tunability in two-terminal oxide-based memristors.
Keywords: Active material; Electron-beam; Memristor; Multi patterns; Multilevel memory; Multipattern memory processing; Regulated memristor; Site-specific; Site-specific conductance; Specific conductance; Artificial Intelligence; Electrons; Neural Networks, Computer; Synapses; electron-beam; multilevel memory; multipattern memory processing; oxygen vacancies; regulated memristors; site-specific conductance